2012
DOI: 10.1016/j.cgh.2012.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Protects Against Barrett's Esophagus in a Multivariate Logistic Regression Analysis

Abstract: Background & Aims Better criteria are needed to identify patients that should be screened for Barrett’s esophagus (BE), to reduce over-testing and improve the cost effectiveness. There is evidence that chemopreventive agents such as non-steroidal anti-inflammatory drugs—particularly aspirin—reduce the risk of esophageal adenocarcinoma (EAC), but little is known about their effects on BE. We analyzed characteristics of patients with BE for factors that might be used in screening and management. Methods In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
3
36
1
Order By: Relevance
“…A considerable amount of experimental data show that COX inhibitors, such as aspirin, reduce malignant behaviour such as proliferation and also induce apoptosis in OAC and non-neoplastic Barrett's cell lines, and nonspecific COX and COX-2 selective inhibitors block the effects of leptin in cell-line models [Ogunwobi and Beales, 2008b;Fang et al 2011;Beales and Ogunwobi, 2010]. Although more definitive conclusions on the preventative effects of aspirin may have to wait until the AspECT trial has reported [Das et al 2009], in observational studies and meta-analyses aspirin use has been reported to be associated with a reduced incidence of both BO and OAC [Omer et al 2012;Beales et al 2013]. Similarly, statins exert potent anticancer effects in OAC cell-line models by inhibiting small signalling G-protein prenylation and limiting procarcinogenic signalling from growth factor receptors [Ogunwobi and Beales, 2008c].…”
Section: Implications For Therapymentioning
confidence: 99%
“…A considerable amount of experimental data show that COX inhibitors, such as aspirin, reduce malignant behaviour such as proliferation and also induce apoptosis in OAC and non-neoplastic Barrett's cell lines, and nonspecific COX and COX-2 selective inhibitors block the effects of leptin in cell-line models [Ogunwobi and Beales, 2008b;Fang et al 2011;Beales and Ogunwobi, 2010]. Although more definitive conclusions on the preventative effects of aspirin may have to wait until the AspECT trial has reported [Das et al 2009], in observational studies and meta-analyses aspirin use has been reported to be associated with a reduced incidence of both BO and OAC [Omer et al 2012;Beales et al 2013]. Similarly, statins exert potent anticancer effects in OAC cell-line models by inhibiting small signalling G-protein prenylation and limiting procarcinogenic signalling from growth factor receptors [Ogunwobi and Beales, 2008c].…”
Section: Implications For Therapymentioning
confidence: 99%
“…A case-control study from Ireland demonstrated NSAIDs to have a protective effect on the development of BE [32], and another case-control study from the USA found that the use of ASA appeared to reduce the risk of BE [34]. On the other hand, a casecontrol study from Australia found no significant association between NSAID use and BE [33].…”
Section: Discussionmentioning
confidence: 92%
“…Studies investigating non-selective COX inhibitors and NSAIDs for BE chemoprevention yielded conflicting results [32][33][34][35]. A case-control study from Ireland demonstrated NSAIDs to have a protective effect on the development of BE [32], and another case-control study from the USA found that the use of ASA appeared to reduce the risk of BE [34].…”
Section: Discussionmentioning
confidence: 94%
“…One further study has attempted to examine the effects of the use of statins on the incidence of Barrett's esophagus. Omer et al reported that statin use was associated with a reduced rate of new diagnoses of Barrett's esophagus in the initial univariate analysis (OR 0.72 (95% CI 0.52 -0.98)) but the statistical significance of this finding was not confirmed in the multivariate analysis (aOR 0.79 (95% CI 0.54 -1.2) (22). Inaccuracies may be inherent in this study due to the purely retrospective nature of the data collection, lack of data on initiation of, or duration of statin use, relying on tertiary care centre endoscopy controls and the lack of matching in between cases and controls (there were significantly more females in the control group).…”
Section: Discussionmentioning
confidence: 99%